PENGARUH LITERASI KEUANGAN SYARIAH, PROMOSI, KUALITAS PELAYANAN TERHADAP KEPUTUSAN MAHASISWA MENJADI NASABAH PADA PERBANKAN SYARIAH - Harish Muhammad Ramadhani, (2021)
This study aims to analyze and explain how the influence of Islamic financial literacy, promotion, and service quality on the decisions of students living in South Tangerang to become customers in Islamic Banking. The sample in this study were active students domiciled in South Tangerang aged 17-23 years and had become customers of Islamic banking. Data collection techniques in this study used a questionnaire with a Likert scale. The variable used is the independent variable consisting of Islamic financial literacy, promotion, and service quality, and the dependent variable is the student's decision to become a customer in Islamic Banking. The method in this study uses multiple linear regression analysis techniques, validity & reliability tests, and hypothesis testing using the SPSS 28 data processing program. Data collection was carried out by questionnaires distributed directly to students domiciled in South Tangerang as many as 113 questionnaires. The results of this study indicate that Islamic financial literacy, promotion, and service quality have a significant partial and simultaneous effect on the decision of students living in South Tangerang to become customers in Islamic Banking.